Learner Perspective on English Pronunciation Teaching in an EFL Context - Tergujeff, Elina (Research in Language, 2013)
This paper reports on an interview study with EFL learners that aimed to explore learners’ perceptions and views on English pronunciation teaching. The participants of the present study were ten EFL learners studying in the public educational system of Finland. Six of the participants were pupils attending basic education class nine, i.e. 15- to 16-year-old lower secondary level pupils. Two were primary level pupils attending basic education class four (aged 10), and two were upper secondary school pupils (aged 18). The interviews were thematic, and the learners were encouraged to speak freely about the English pronunciation teaching they were receiving and their opinions on this. In addition, they were asked to discuss their goals in English pronunciation, and to consider their pronunciation learning in class and out of class. The interviews were part of a wider study, mapping English pronunciation teaching practices in the context of Finnish schools. On the basis of the findings, the learners do not seem to have aspirations to native-like pronunciation, but rather aim at achieving intelligible and fluent speech. Only few reported an accent preference (British or American). The primary level learners expressed satisfaction with the amount of pronunciation teaching, whereas most of the lower and upper secondary level learners claimed that pronunciation teaching was insufficient. Despite their criticisms of their pronunciation teaching, the learners reported that they had learnt English pronunciation at school. In addition, many of the learners described learning pronunciation outside school, e.g. through media and personal encounters.